Biofilm formation risk assessment for psychrotrophic Pseudomonas in raw milk by MALDI-TOF mass spectrometry. (15th February 2023) - Yan, Minghui; Luo, Liwen; Li, Dandan; Liu, Zhenmin; Wei, Ran; Yi, Jia; Qiao, Liang; You, Chunping
Abstract: Psychrotrophic Pseudomonas is often found as the predominant bacteria causing the spoilage of raw milk during product processing and storage. The spoilage can be aggravated if the strains have biofilm-forming ability. Risk assessment of biofilm formation by psychrotrophic Pseudomonas is highly important to prevent product spoilage at early stage. Herein, we develop an efficient strategy to identify the biofilm-forming risk by psychrotrophic Pseudomonas in raw milk based on MALDI-TOF MS. Molecular mass fingerprinting of whole cells was collected by MALDI-TOF MS, followed by multivariate statistical analysis combined with machine learning to establish a classification model of biofilm-forming ability by psychrotrophs. The results showed that Pseudomonas with different biofilm-forming capabilities can be well discriminated by the MALDI-TOF MS molecular mass fingerprinting. A classification model was established, showing 100% accuracy in biofilm-forming risk identification. Highlights: A MALDI-TOF MS-based strategy to assess the biofilm-forming risk of Pseudomonas. MALDI-TOF MS was combined with multivariate statistical analysis and machine learning. A classification model at strain level based on MS was established. This strategy enables rapid and efficient microbial risk recognition in milk industry. Protein biomarkers associated with the biofilm formation ability of the psychrotrophic isolates were identified.